Where there's fire, there's Smoke : Smoke Jensen, the last mountain man - Johnstone, William W.; Johnstone, J. A. (Pinnacle western., 2016)
His country burning with war, his family shattered, a young man strikes off on his own and builds a legend with his fists, a pistol, knife, and long gun. This collection includes the classic westerns Trail of the Mountain Man and Return of the Mountain Man, long unavailable and here together for the first time in one action-packed volume ...